A Facile Method to Coat Nanoparticles with Lipid Bilayer Membrane: Hybrid Silica Nanoparticles Disguised as Biomembrane Vesicles by Particle Penetration of Concentrated Lipid Layers. Issue 12 (12th January 2023) - Mizuta, Ryosuke; Inoue, Fumihito; Sasaki, Yoshihiro; Sawada, Shin‐ichi; Akiyoshi, Kazunari
Abstract: Natural membrane vesicles, including extracellular vesicles and enveloped viruses, participate in various events in vivo. To study and manipulate these events, biomembrane‐coated nanoparticles inspired by natural membrane vesicles are developed. Herein, an efficient method is presented to prepare organic–inorganic hybrid materials in high yields that can accommodate various lipid compositions and particle sizes. To demonstrate this method, silica nanoparticles are passed through concentrated lipid layers prepared using density gradient centrifugation, followed by purification, to obtain lipid membrane‐coated nanoparticles. Various lipids, including neutral, anionic, and cationic lipids, are used to prepare concentrated lipid layers. Single‐particle analysis by imaging flow cytometry determines that silica nanoparticles are uniformly coated with a single lipid bilayer. Moreover, cellular uptake of silica nanoparticles is enhanced when covered with a lipid membrane containing cationic lipids. Finally, cell‐free protein expression is applied to embed a membrane protein, namely the Spike protein of severe acute respiratory syndrome coronavirus 2, into the coating of the nanoparticles, with the correct orientation. Therefore, this method can be used to develop organic–inorganic hybrid nanomaterials with an inorganic core and a virus‐like coating, serving as carriers for targeted delivery of cargos such as proteins, DNA, and drugs. Abstract : Here, nanoparticles are efficiently coated with a lipid bilayer by passing them through a concentrated lipid layer prepared by density gradient centrifugation. In addition, a new approach for the synthesis of bioinorganic hybrid nanomaterials is demonstrated by applying cell‐free protein expression to embed membrane proteins, the Spike protein of severe acute respiratory syndrome coronavirus 2, into coatings of the nanoparticles.